Flexible and biodegradable film for environmental friendly packaging material - Ali, Fathilah; Anuar, Hazleen; Awale, Rania J. (2015)
Petroleum based packaging materials has been a problem due to its non-degradation nature. Polylactic acid is a polymer from renewable resources and has properties comparable to conventional plastics. Our research aims are to improve the general properties of PLA and reduce the cost of PLA by blending with starch as filler and epoxidized palm oil (EPO) as plasticizer. The PLA/starch/EPO blends were prepared by melt blending methods and their thermal and mechanical properties were investigated by Differential Screening Calorimetry (DSC) and Universal Tensile Machine (UTM).